Building Orchestration of the Logistics Industry Through the Creation of a Services Ecosystem in Indonesian Freight Forwarder Companies - Setia Wiguna, Esa; Thamrin, HM.; Abdul Majid, Suharto; Tatiana, Yana (Dinasti Publisher, 2024)
Abstract: In the last seven to eight years, there have been three disruptions at once: Digital Disruption, Millennial Disruption, and Pandemic Disruption. Relevant to the three disruptions which are also accompanied by changes in consumer behavior, the freight forwarding industry in Indonesia needs to transform from services product to services ecosystem. This can provide value to stakeholders in the freight forwarding industry in particular and the logistics industry in general, including transportation service providers (land, sea, air, train), warehousing, stevedoring, heavy equipment rental, custom clearance handling, banking, digital payment services, quarantine services, and the customers themselves. This study aims to gain a deeper and more understanding of Service Quality, Brand Image, and Price, in the creation of a services ecosystem in Indonesian Freight Forwarding Companies to build an orchestration of the stakeholders in the Logistics Industry. Keyword: Keywords: Service Quality, Brand Image, Price, Ecosystem, Freight Forwarding, Orchestration, Creation.